Design, synthesis and biological evaluation of novel inhibitors against cyanobacterial pyruvate dehydrogenase multienzyme complex E1. Issue 12 (15th June 2019) - Feng, Jiangtao; He, Haifeng; Zhou, Yuan; Guo, Xiaoliang; Liu, Honglin; Cai, Meng; Wang, Fang; Feng, Lingling; He, Hongwu
Graphical abstract: Abstract: Cyanobacterial pyruvate dehydrogenase multienzyme complex E1 (PDHc E1) is a potential target enzyme for finding inhibitors to control harmful cyanobacterial blooms. In this study, a series of novel triazole thiamin diphosphate (ThDP) analogs were designed and synthesized by modifying the substituent group of triazole ring and optimizing triazole-benzene linker as potential cyanobacterial PDHc E1 (Cy-PDHc E1) inhibitors. Their inhibitory activities against Cy-PDHc E1 in vitro and algicide activities in vivo were further examined. Most of these compounds exhibited prominent inhibitory activities against Cy-PDHc E1 (IC50 1.48–4.48 μM) and good algicide activities against Synechocystis PCC6803 (EC50 0.84–2.44 µM) and Microcystis aeruginosa FACHB905 (EC50 0.74–1.77 µM). Especially, compound8d showed not only the highest inhibitory activity against Cy-PDHc E1 (IC50 1.48 μM), but also the most powerful inhibitory selectivity between Cy-PDHc E1 (inhibitory rate 98.90%) and porcine PDHc E1 (inhibitory rate only 9.54%). Furthermore, the potential interaction between compound8d and Cy-PDHc E1 was analyzed by a molecular docking method and site-directed mutagenesis and enzymatic analysis and fluorescence spectral analysis. These results indicated that compound8d could be used as a hit compound for further optimization and might have potential to be developed as a new algicide.